THE EFFECTIVENESS OF FAMILY MENTORING MODEL TO DECREASE BLOOD PRESSURE OF HYPERTENSIVE CLIENTS - Ibnu, Faisal Faisal; Nur Hidayati , Rina; Wahyuni , Lutfi (Universitas Airlangga, 2023)
Introduction: Hypertension is the most common disease and usually arises without complaints so many clients do not know that they have suffered from hypertension. Until now Hypertension is still a major problem and is the first cause of death in the world. This study aims to find out the Effectiveness of Family Mentoring Model against decreased Blood Pressure of hypertensive clients. Method: The research design used quasi-Randomized Control Group Pre-Test Post Test Design experiments on 120 hypertensive clients using purposive sampling. Model interventions are given for 8 weeks, and home visits are made once a week. Data analysis using independent and dependent t tests. Result: The results showed that the model intervention effectively lowers the blood pressure of hypertensive clients. This was indicated by a systolic blood pressure decrease of 18.8 mmHg significantly after the model intervention and significantly different (p_value : 0.0001). Conclusion: Diastolic blood pressure showed a significant decrease of 11.1 mmHg after model intervention and significantly different (p_value : 0.0001). This model is recommended to be implemented in all areas of work of public health centers as an effort to control hypertension.